Intracardiac Migration Following Percutaneous Computed Tomography-Guided Fiducial Marker Implantation for Pulmonary Metastasis: A Rare Complication - Duaa Alhindi; Yousof AbdulRahman Al Zahrani; Azzam Khankan (The Arab Journal of Interventional Radiology)
A 41-year-old female with rectal cancer and lung metastasis underwent percutaneous transthoracic placement of fiducial marker. Postprocedure scan showed the migration of one of the fiducial markers to the left ventricle. Intracardiac fiducial marker migration is a rare complication but can happen, especially with centrally located lesions. Physicians and patients should be aware of this risk.